Propositions, functions, and analysis selected essays on Russell's philosophy - Hylton, Peter (Oxford : Clarendon Press, 2010)
The work of Bertrand Russell has a decisive influence on the emergence of analytic philosophy, and on its subsequent development. The essays in this text recapture aspects of Russell's philosophical vision during his most influential period, the two decades following his break with Idealism in 1899.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Russell, Bertrand, -- 1872-1970.; Analysis (Philosophy) -- History -- 20th century; Logic, Symbolic and mathematical -- History -- 20th century